Recruitment of the mitotic exit network to yeast centrosomes couples septin displacement to actomyosin constriction. Issue 1 (December 2018) - Tamborrini, Davide; Juanes, Maria; Ibanes, Sandy; Rancati, Giulia; Piatti, Simonetta
Abstract In many eukaryotic organisms cytokinesis is driven by a contractile actomyosin ring (CAR) that guides membrane invagination. What triggers CAR constriction at a precise time of the cell cycle is a fundamental question. In budding yeast CAR is assembled via a septin scaffold at the division site. A Hippo-like kinase cascade, the Mitotic Exit Network (MEN), promotes mitotic exit and cytokinesis, but whether and how these two processes are independently controlled by MEN is poorly understood. Here we show that a critical function of MEN is to promote displacement of the septin ring from the division site, which in turn is essential for CAR constriction. This is independent of MEN control over mitotic exit and involves recruitment of MEN components to the spindle pole body (SPB). Ubiquitination of the SPB scaffold Nud1 inhibits MEN signaling at the end of mitosis and prevents septin ring splitting, thus silencing the cytokinetic machinery. The Mitotic Exit Network (MEN) promotes mitotic exit and cytokinesis but if and how MEN independently controls these two processes is unclear. Here, the authors report that MEN displaces septins from the cell division site to promote actomyosin ring constriction, independently of MEN control of mitotic exit.